Retroperitoneal Paraganglioma Presenting as a Chest Pain: A Case Report - Parag Brahmbhatt; Pranav Patel; Atif Saleem; Rathi Narayan; Mark Young (Case Reports in Oncological Medicine)
Paragangliomas are very rare tumors derived from neuroendocrine cells of autonomic nervous system. Extra-adrenal paragangliomas account for only 10 to 15% of all paragangliomas and may present incidentally as a mass. Typical triad of fluctuating hypertension, headache, and sweating is not always present which makes the diagnosis difficult sometimes. Definitive diagnosis is usually made with histologic findings and surgery is the treatment of choice. We report a case of a 53-year-old male who presented with chest pain and vomiting.